Lymphocyte to C-Reactive Protein Ratio as an Early Biomarker to Distinguish Sepsis from Pneumonia in Neonates - Liu X; Mu Y (Dove Medical Press, 2023)
Xinrui Liu,1 Yuan Mu2 1Zhengzhou Key Laboratory of Children's Infection and Immunity, Children's Hospital Affiliated to Zhengzhou University, Henan Children's Hospital, Zhengzhou Children's Hospital, Zhengzhou, People's Republic of China; 2Institute of Thermology, Henan Institute of Metrology and Testing Sciences, Zhengzhou, People's Republic of ChinaCorrespondence: Xinrui Liu, Email 13526523661@163.comBackground: Neonatal sepsis is an acute and severe disease that seriously threatens the life and health of newborns. Neonates with pneumonia may also have unrecognized neonatal sepsis. Early diagnosis of neonatal sepsis is beneficial for early treatment. This study aimed to evaluate the clinical significance of the lymphocyte-to-C-reactive protein ratio (LCR) as an early biomarker to distinguish sepsis from pneumonia.Methods: This retrospective study enrolled 1635 neonates with pneumonia from February 2016 to March 2022. Among them, 182 cases were diagnosed with sepsis based on the positive blood culture results. Clinical and laboratory data were extracted from the electronic medical records. LCR was calculated as the ratio of the total lymphocyte count (× 109 cells/L) to the C-reactive protein level (mg/L). Binary logistic regression analysis was conducted to evaluate the clinical significance of LCR as an early biomarker in distinguishing sepsis from pneumonia. Receiver operating characteristic (ROC) analysis was performed to assess the diagnostic value of LPCR in sepsis cases. All statistical analyses were conducted using Statistical Product and Service Solutions, version 24.0.Results: The neonates with pneumonia combined with sepsis had a lower LCR than that of the neonates with pneumonia. Further analysis showed that the prevalence of neonatal pneumonia combined with sepsis was significantly higher in the low-LCR group than in the high-LCR group (20.7% vs 5.5%, P < 001). Binary logistic regression revealed that LCR was an independent risk factor for identifying pneumonia combined with sepsis. The ROC curve analysis revealed that LCR had better power than the lymphocyte count and CRP level individually in diagnosing neonatal pneumonia combined with sepsis (0.72 vs 0.65 vs 0.66, P < 0.001), with 62% sensitivity and 72% specificity.Conclusion: LCR can be a potential early biomarker in distinguishing neonates with sepsis from those with pneumonia.Keywords: lymphocyte to C-reactive protein ratio, neonates, pneumonia, sepsis